PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Raga Ramadhan; Sutris no (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to examine the effect of financial performances reflected in financial ratios which are PER, EPS, DER, ROA, and ROE on stock prices of the Indonesian manufacturing companies listed in Indonesian Stock Exchange. Purposive sampling method is used to select samples and there are 120 companies chosen as samples for the period of 2009 - 2011. Statistical method that used in this study is multiple regression. The results show that all of the independent variables which are PER, EPS, DER, ROA, and ROE affect significantly the stock prices and it also finds that DER is the most influencing ratio compared others. From that result, it can be concluded that investors who will put their funds in the capital market need to consider the PER, EPS, DER, ROA and ROE in order to not loss their investment.   Key words: Financial performance, stock prices, manufacturing companies